Transgender and Covid-19: The Disparity of Government’s Policy Partiality in North Sumatra - Asihna Riris Pasaribu , Vera; Manullang, Jonathan; Hamonangan Sinurat , Paska (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
This research was motivated by the devastating impact of Covid-19 global pandemic towards the daily lives of transgender individuals in North Sumatra. The aim of this research is to capture the reality of how far the government has protected and aided transgender people through various policies that have been launched from April 2020 to October 2021. By using a qualitative approach this research combines data collection from in-depth interviews and literature studies. The authors find that transgender people in North Sumatra are heavily relying on the evident solidarity and meaningful initiatives from their respective communities in order to survive during this horrible pandemic. Therefore, we argue that the so-called public policies from the North Sumatran government at all levels, including Covid-19 vaccination distribution scheme, have failed to fulfill the urgent needs of the transgenders.